Fede, Diritto E Giustizia in Dante - Bianchini, Daniela (Lateranum, 2023)
Dante Alighieri was not a jurist, however his works contain numerous legal references of great interest. Justice is one of the central themes of Alighieri's works, and in particular of the Divine Comedy, where he closely relates it to charity. Dante's conception of justice explains the reasons for the Poet's opposition to a certain way of understanding law and being a jurist, as well as his indignation for the indolent. 2021 is the year of the seventh centenary of the death of Alighieri and coincides with the beatification of Rosario Angelo Livatino, the first Blessed magistrate in the history of the Church and the one who certainly knew how to embody that model of a jurist indicated by Alighieri, in the way in which he knew how to unify justice and charity. (English)